Case report and diagnostic implications of misdiagnosis of pericardial myxoid liposarcoma by multimodal imaging - Wang, Juan; Zhu, Xi-Jun; Sun, Li-Xia; Song, Yu-Ling; Wu, Lai; Cao, Yun-Long; Xue, Xin-Yu; Wang, Dong; Liu, Qian (Frontiers in Cardiovascular Medicine, 2025)
Myxoid liposarcoma (MLPS) typically occurs in the extremities. Pericardial involvement is exceptionally rare and usually indicates metastatic disease. Because of their non-specific imaging features, such lesions are often mistaken for benign tumors, leading to diagnostic errors. This report describes the case of a 69-year-old woman who presented with chest tightness and had a history of gluteal MLPS. Multimodal imaging (CT, ultrasound, MRI) revealed a pericardial mass. Although features such as well-circumscribed margins and delayed contrast filling suggested a benign-appearing lesion rather than enabling a definitive diagnosis, the clinical history of the patient strongly favored metastatic MLPS. Imaging alone could not provide a definitive diagnosis, highlighting the challenge posed by overlapping features between benign and malignant cardiac masses. The final diagnosis relied on histopathology and molecular testing. Postoperative immunohistochemistry revealed a spindle cell tumor with myxoid stroma (S-100 negative, MDM2 weakly positive). Molecular pathology confirmed the diagnosis by detecting the FUS-DDIT3 fusion gene, establishing metastatic MLPS. This case underscores the critical limitations of imaging in reaching a definitive diagnosis and emphasizes that accurate classification necessitates integration with histopathological and molecular analyses. An optimized diagnostic strategy should incorporate a comprehensive review of clinical history—especially any prior sarcoma—maintain heightened vigilance for overlapping imaging features of rare sarcomas in atypical locations, and include molecular pathology to effectively prevent misdiagnosis.